(untitled) (Delta Medical College Journal, 2014)
Guillain-Barré syndrome (GBS), a neurologic disease that produces ascending paralysis, affects people all over the world. Acute infectious illness precedes 50%-75% of the GBS cases. Although many infectious agents have been associated with GBS, the strongest documented association is with Campylobacter infection. The first line of evidence supporting Campylobacter infection as a trigger of GBS is anecdotal reports. The second line of evidence is serological surveys, which have demonstrated that sera from GBS patients contain anti Campylobacter jejuni antibodies, consistent with recent infection. Finally, culture studies have proven that a high proportion of GBS patients have C. jejuni in their stools at the time of onset of neurological symptoms. One of every 1058 Campylobacter infections results in GBS. Sialic acid containing lipooligosaccharides (LOS) biosynthesis gene locus are associated with GBS and the expression of ganglioside mimicking structures. GM1a was the most prevalent ganglioside mimic in GBS associated strains. Molecular mimicry between C. jejuni LOS and gangliosides in human peripheral nerves, and cross-reactive serum antibody precipitate the majority of GBS cases in Bangladesh, like worldwide. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17794 Delta Med Col J. Jan 2014; 2(1): 28-35